1994
DOI: 10.1161/01.str.25.12.2331
|View full text |Cite
|
Sign up to set email alerts
|

Development of aspirin resistance in persons with previous ischemic stroke.

Abstract: Background and Purpose The ex vivo effect of aspirin (ASA) on platelet aggregation, the platelet component of thrombosis, was studied at repeated intervals in a cohort of patients taking aspirin for recurrent ischemic stroke prevention to define the maintenance of efficacy over time.Methods We administered increasing doses of aspirin (from 325 to 1300 mg/d) to patients with previous ischemic stroke and determined the extent of inhibition of platelet aggregation after 2 weeks and thereafter at approximately 6-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
229
2
13

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(251 citation statements)
references
References 17 publications
4
229
2
13
Order By: Relevance
“…Two reports showed that the extent of inhibition of platelet aggregation by aspirin progressively decreased over time in some patients, suggesting that some kind of aspirin tolerance may develop during chronic aspirin treatment. 50,75 This issue is controversial, because another study showed that 100 patients on chronic aspirin treatment had consistently reduced platelet aggregation over time. 76 …”
Section: Unproven Aspirin Resistancementioning
confidence: 99%
“…Two reports showed that the extent of inhibition of platelet aggregation by aspirin progressively decreased over time in some patients, suggesting that some kind of aspirin tolerance may develop during chronic aspirin treatment. 50,75 This issue is controversial, because another study showed that 100 patients on chronic aspirin treatment had consistently reduced platelet aggregation over time. 76 …”
Section: Unproven Aspirin Resistancementioning
confidence: 99%
“…It is unclear if these observations reflect absorption problems or altered pharmacodynamics. 27,34 Aspirin in hypertensive patients: clinical implications and future research Coronary artery and cerebro-vascular diseases are the most common serious complications of long standing hypertension. The widespread use of aspirin probably contributes significantly to reduction of cardiovascular morbidity and mortality among high risk hypertensive patients with concomitant cardiovascular problems 35 and therefore there is a great potential for combined treatment with aspirin and ACE-I.…”
Section: Ace-i Induced Cough As a Clinical Marker Of Ace-i Activitymentioning
confidence: 99%
“…Despite its large use, there are concerns about the efficacy of aspirin and methods to evaluate it [2,3]. Indeed, it appears that the antiplatelet effect of aspirin is not uniform in all patients and previous studies estimated that 8-45% of the population were aspirin resistant [4][5][6][7][8]. Most studies have focused on patients with coronary artery disease, although a few reports have identified aspirin resistance in patients with stroke or cerebrovascular disease [6][7][8][9].…”
Section: )1mentioning
confidence: 99%
“…Typically blood group O is associated with lower plasma VWF levels compared with non-O blood groups [4]. Non-O blood groups have also been shown to be associated with a higher incidence of CAD [5], which could in turn be determined by higher circulating VWF levels [7]. Inflammatory cytokines such as interleukin-1 and tumor necrosis factor-a [8] as well as procoagulant factors such as thrombin can influence the release of VWF from ECs [9].…”
Section: )1mentioning
confidence: 99%